Dynamiccs of Asian Savings : Role of Growth and Age Structure. (IMF Working Papers; Working Paper, 1988)
This paper shows how growth and demography, two important determinants of the savings rate in the life-cycle approach, explain a large part of the diversity in savings behavior in Asia across eight countries as well as over time. Inflation and adverse movements in the terms of trade are found to be two additional factors with depressing effects on the propensity to save. The paper also finds evidence in favor of the error-correction formulation under which the savings rate varies procyclically in the short run but remains constant in the steady state.